Laptops for dummies® - Gookin, Dan (--For dummies., 2016)
The fast and easy way to get up and running with a laptop Are you new to the world of laptops? You've come to the right place! Laptops For Dummies covers the many topics and issues unique to laptops, including synchronizing with the desktop, coordinating email pick-up between two machines, remotely accessing the desktop, networking, power management, storage, security, and more. This new edition also provides updates to cover the latest technology, current processors, and steps to update memory and hard drive capacities. In business-while they spend most of their time in a desktop docking station-laptops are absolutely essential for providing mobility to professionals. In the home, they've begun to replace desktop PCs, as they now offer larger displays, longer battery power, and speeds equal to desktop computers. Plus, you can do just about everything with a laptop that you can do with a traditional desktop, minus the big, bulky machine and multiple cords. If you're just making the switch over to a laptop, this hands-on, easy-to-follow guide makes the transition easy! Covers the latest hardware and technology updates you need to get up and running with your laptop Includes updates on the new Windows 10 operating system, wireless networking, smartphone tethering, and using productivity applications on laptops Walks you through everything you need to deal with add-ons, networking procedures, and connectivity and communication Presents complex material in a way that makes it simple and accessible Whether you've never logged onto a laptop or are just looking to stay up-to-date with the latest information on operating systems and software, Laptops For Dummies has you covered.